2021
DOI: 10.3934/cpaa.2020282
|View full text |Cite
|
Sign up to set email alerts
|

Semilinear Caputo time-fractional pseudo-parabolic equations

Abstract: This paper considers two problems: the initial boundary value problem of nonlinear Caputo time-fractional pseudo-parabolic equations with fractional Laplacian, and the Cauchy problem (initial value problem) of Caputo time-fractional pseudo-parabolic equations. For the first problem with the source term satisfying the globally Lipschitz condition, we establish the local well-posedness theory including existence, uniqueness and regularity of the local solution, and the further local existence theory related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 54 publications
(79 reference statements)
1
22
0
1
Order By: Relevance
“…Basic settings. (see [3]) We first consider the spectral problem for the negative Laplacian on a bounded domain D ⊂ R N as follows…”
Section: Preliminary Materialsmentioning
confidence: 99%
“…Basic settings. (see [3]) We first consider the spectral problem for the negative Laplacian on a bounded domain D ⊂ R N as follows…”
Section: Preliminary Materialsmentioning
confidence: 99%
“…Because the fractional derivative will help us to capture the viscoelastic properties of the flow, the time-fractional pseudo-parabolic equations are useful for describing the behavior of some non-Newtonian fluids. In mathematical aspect, it is a hot stream to consider the time-fractional version of the classical mathematical models including the parabolic type equation [25], the time-space fractional Shrödinger equation with polynomial type nonlinearity [14], the time-fractional Navier-Stokes equations (FNS) [13], and also the time-fractional pseudo-parabolic equations [24]. Surprisingly in [13], it was shown that the order of time-fractional derivative influences the regularity not only in time variable but also in the spatial variable.…”
mentioning
confidence: 99%
“…Surprisingly in [13], it was shown that the order of time-fractional derivative influences the regularity not only in time variable but also in the spatial variable. In [24], a first attempt to explore the influence of the degree of nonlinearity on the dynamic behavior of the solution was conducted by considering the logarithmic nonlinearity and globally Lipschitz nonlinearity. All of the above achievements in this direction pushed us to consider not only the influence of the degree of the nonlinearities but also the order of the time-fractional derivative on the behavior of the solution to the time-fractional pseudo-parabolic equations with four distinguished types of nonlinearities, in which the degree of nonlinearities increase gradually.…”
mentioning
confidence: 99%
“…This derivative has interesting advantages, which can be seen in the Introduction of [38]. A good understanding for subdiffusion second parabolic equation with Caputo derivative can be found in [3,4,11,21,30,20] and references therein. Regarding the good works on the existence of solutions of nonlinear diffusion equation with Caputo-Fabrizio operator are typical articles such as [32,38].…”
mentioning
confidence: 99%
“…The main contribution of this paper is described in detail as follows The key tool evaluation relies on L p − L q estimates for solution operators, where we used a lemma about L p − L q for semigroup of biharmonic operator taken in the paper [17]. Part of this technique is learned from the interesting recent work of Tuan-Au-Xu [30]. To be successful in our evaluations we also need a good understanding of the embedding between Hilbert scales and L p spaces.…”
mentioning
confidence: 99%